AN ANALYSIS OF HIGHER ORDER THINKING SKILL (HOTS) IN ENGLISH SUMMATIVE TEST ITEMS PREPARED BY TEACHERS OF SMK TELKOM PEKANBARU - Fadillah, Miftahul; Supriusman, Supriusman; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aims to find out how many test items of HOTS in summative tests are prepared by teachers of SMK TELKOM Pekanbaru. The object of this study was the odd and even semester of summative test items of grade X students for the 2022/2023 school year. This research used descriptive quantitative research. The data was gathered through a documentation study, namely the document in the form of a School Examination question sheet. The data were analyzed and categorized based on the C1-C6 thinking level, and then calculated the percentage of questions with the HOTS category based on the formula according to Ali (2013: 201) using Microsoft Excel. The result of the study revealed that there were 43 questions or 45.55%, with details of 22 questions in the odd semester or 48.88% which included C4 (analyze) questions totaling 15 questions, C5 (evaluate) totaling 5 questions, and C6 (create) totaling 2 questions. In the even semester summative test there were 19 questions or 42.22% which included C4 (analyze) questions totaling 13 questions, C5 (evaluate) totaling 4 questions, and C6 (create) totaling 2 question. Each semester was in the